Development of a STEM-Based Learning Module on Heat And Temperature to Improve Students’ Scientific Literacy - ika annisa; Syubhan Annur; Yasmine Khairunnisa (International Journal of Education, Language, and Social Science, 2025)
Scientific literacy is the ability of students to understand, explain scientific phenomena, and use scientific knowledge in decision making, however the scientific literacy of students in Indonesia is still relatively low. This development research aims to analyze the validity, practicality, and effectiveness of learning modules with a STEM approach to temperature and heat material to improve scientific literacy of grade VII junior high school students. This study uses the 4D development model (Define, Design, Develop, and Disseminate). The module product was tested on 10 students in a small group trial and 28 students in a large class trial at SMP Negeri 27 Banjarmasin. The data were analyzed descriptively with validity analysis techniques using the Aiken's V formula, practicality analysis based on the percentage of student response questionnaires, and effectiveness analysis using the N-Gain value from the pretest and posttest results. The results showed that the learning module obtained a validity score of 0.92 (very valid), practicality of 90.54% (very practical), and N-Gain of 0.84 (high category). Based on these results, the STEM-based learning module is feasible to use, practical and effective in improving students' scientific literacy